The effectiveness of the rules of international humanitarian Law in protecting journalists - فاضل زهره; مايا شوكت صفطلي (Latakia University Journal - Economic and Legal Sciences Series, 2023)
In the eyes of many, war is a social phenomenon since ancient times, and it has evolved a lot through the development of life, which necessitated the creation of a law that protects groups that do not participate in this war, and among these groups are journalists. It attaches special importance to preserving the safety and security of the journalist when he communicates the truth to people without being exposed to any danger, because his work in covering the events of the armed conflict and transmitting news to societies all over the world may expose him to many dangers due to the nature of his profession . International humanitarian law, as the special law applied during the period of armed conflicts, pledged to protect this group. However, the results we are witnessing on the ground remain disastrous because the parties to the conflict often target journalists by killing, kidnapping, or arresting for various reasons. Although the international community did not stop at the limits of international conventions to protect journalists, rather its efforts were crystallized through international bodies and non-governmental organizations that healed the wounds of journalists and provided them with many means of survival during armed conflicts.